A Legal Analysis on Online Fraud Using Fake Identity - Hasibuan, Juneidi; Syam, Syafrudin (Indonesian Journal of Multidisciplinary Science, 2023)
This study aims to analyze the legal accountability for online fraud using fake identities, also known as catfishing. The phenomenon of catfishing has become increasingly prevalent with the advancement of information technology, particularly in the use of social media and online dating applications. The practice of online fraud using fake identities has detrimental emotional, psychological, and financial impacts on victims.The research method used is document analysis and literature review. Through document analysis, the researcher analyzes relevant texts and legal documents such as laws, regulations, court decisions, and government policies related to online fraud and fake identities. Meanwhile, through literature review, the researcher searches for and reviews relevant literature on the legal aspects of online fraud and fake identities.The research findings indicate that catfishing can be a violation of the law depending on the country and jurisdiction in place. Some countries have adopted laws that regulate online fraud and the misuse of fake identities. However, identifying catfish perpetrators and enforcing related laws often proves to be challenging as they employ various means to conceal their true identities in the virtual world. The legal accountability for online fraud using fake identities needs to be acknowledged and strengthened. In this regard, law enforcement and prosecution of catfish perpetrators are crucial to protect society from online fraud practices. Additionally, prevention and protection efforts involving education and public awareness regarding the risks and preventive measures against catfishing should also be enhanced.